The Effectiveness of the Simulation Method on Students’ Qur’anic Literacy: A Classroom Action Research Study at MTs Negeri Batu Bara Regency - Fitri Yanti (Yayasan Bayt Shufiya Nusantara, 2023)
The low level of Qur’anic literacy is often rooted in methodological stagnation that traps students in textual boredom. This study aimed to examine the effectiveness of the simulation method in improving students’ Qur’anic reading and writing skills (Baca Tulis Al-Qur’an/BTA) at MTs Negeri Batu Bara Regency. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles involving 36 students as research participants. Data collection instruments consisted of cognitive-practical ability tests and observation sheets assessing teacher and student activities. The findings demonstrated a highly significant and progressive improvement in learning outcomes. The class average score increased from 55.83 in the pre-cycle stage to 75.83 in Cycle I, and reached 89.72 at the end of Cycle II. Classically, the learning mastery percentage rose sharply from 36.11% to 94.44%, indicating that the simulation method successfully transformed theoretical understanding into well-established motoric competencies. This study concludes that the simulation method is effective in addressing the challenges of Qur’anic reading and writing instruction through strengthening habituation aspects (ta‘wid) and encouraging active student engagement. The implications of these findings recommend the use of simulation as a primary instructional strategy for madrasah educators to enhance Qur’anic literacy standards in an applicative and sustainable manner.